(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The British and Balkan Woman: British Perceptions of Balkan Women and Their Femininity in the Long Nineteenth Century (1789–1914) / Melina Rokai. – Beograd: Čigoja štampa, 2017 – 493. ISBN 978-86-531-0285-2